Autologous Platelet-Rich Fibrin (PRF) as an Adjunct in the Management of Osteoradionecrosis and Medication-Related Osteonecrosis of Jaws. Case Series in A Single Centre - Benjie Law (Applied Sciences, 2021)
Osteoradionecrosis (ORN) of the jaws and medication-related osteonecrosis of the jaws (MRONJ) are uncommon but serious diseases affecting the oral and maxillofacial region with clinically similar appearance but distinct pathophysiology. Management of ORN and MRONJ is inherently challenging and the treatment outcomes are unpredictable. The use of autologous platelet concentrates (APCs) to promote hard and soft tissue healing is well described in the literature, and the efficacy of leucocyte and platelet-rich fibrin (L-PRF) has been well documented in a number of clinical studies. The aim of this study was to present our treatment strategy and the outcomes of incorporating L-PRF as a surgical adjunct in management of ORN and MRONJ in our centre. Methods: eight cases of ORN and MRONJ were treated with a combination of sequestrectomy and L-PRF as a surgical adjunct. Results: the overall success was 87.5%. Using L-PRF as an adjunct, we were able to predictably manage ORN and MRONJ without causing significant morbidity. Conclusion: our experience shows that L-PRF may be used as a valuable and cost-effective adjunct to surgical management of ORN and MRONJ. However, due to a limited number of patients, and a short period of review, the true effectiveness of the method is yet to be demonstrated in a longer follow-up study including a greater number of patients, besides the inclusion of a control group.